Single Mode Circular Waveguide Applicator for Microwave Heating of Oblong Objects in Food Research - Kybartas, D.; Ibenskis, E.; Surna, R. (Elektronika ir Elektrotechnika, 2011)
A design of open waveguide resonator for microwave heating of oblong objects is presented in this study. This device is dedicated for research in food industry. In order to avoid misalignment of samples, an axis-symmetric wave mode TM01 is used in waveguide with circular cross-section. This approach allows rapid heating of oblong samples in axial area using relatively low power magnetron. In order to obtain longer zone of heating, an operating frequency was chosen to be near critical. Good agreement between simulated and experimental results was found. Ill. 7, bibl. 11, tabl. 1 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.114.8.701